1992
DOI: 10.1007/bf00188350
|View full text |Cite
|
Sign up to set email alerts
|

Motional narrowing of the 2H NMR spectra near the chain melting transition of phospholipid/D2O mixtures

Abstract: The reduction in spectral splitting, or motional narrowing, of the deuterium spectra of D2O/phospholipid mixtures near the main chain melting phase transition was studied for palmitoyloleoylphosphatidylcholine (POPC), palmitoyloleoylphosphatidylethanolamine (POPE) and equimolar mixtures of the two at 10% hydration. For POPC the splitting was about 1700 Hz in both the fluid and gel phases, dropping to zero near the phase transition (as reported previously). For POPE the splitting remained approximately constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…5 and 6) and 10 wt % water (Fig. 7) are very similar to those of the temperature variation of the quadrupolar splitting of interbilayer D 2 O in PCs and PEs (Pope et al, 1981;Hawton and Doane, 1987;Bryant et al, 1992), as shown in Fig. 2.…”
Section: A Correlation Between the Ordering Of Headgroup And The Ordesupporting
confidence: 76%
See 3 more Smart Citations
“…5 and 6) and 10 wt % water (Fig. 7) are very similar to those of the temperature variation of the quadrupolar splitting of interbilayer D 2 O in PCs and PEs (Pope et al, 1981;Hawton and Doane, 1987;Bryant et al, 1992), as shown in Fig. 2.…”
Section: A Correlation Between the Ordering Of Headgroup And The Ordesupporting
confidence: 76%
“…They ascribed the small Dn of D 2 O to the fast rotation of the O-D bond of the water molecule around an axis that makes nearly a magic angle with the O-D bond. Similarly, we note that Dn of interbilayer D 2 O in PC and PE membranes containing 10 wt % or less water was reported to be \2 kHz (Bryant et al, 1992;Pope et al, 1981), which is much smaller than the static quadrupolar splitting constant of 170 kHz, indicative of a very low ordering of the O-D bond of water. This is inconsistent with the high ordering of headgroups in bilayers of low hydration, e.g., in 10WT and DH DOPC dispersions that we have observed in our present ESR studies.…”
Section: Significance Of the Correlation Between The Ordering Of Headsupporting
confidence: 55%
See 2 more Smart Citations
“…4.23, is slightly disturbed, most probably due to admixture effects (Pfeiffer et al 2010), the parameters A and B are very similar to the original values published before. An important limitation of this method should be mentioned; the quadrupolar splitting is reduced at and in the range of the main phase transition, a phenomenon which is called motional narrowing (Bryant et al 1992). The motional narrowing proceeds over a relatively wide temperature ranges (10-20 K) and its temperature dependency can mathematically be described by Eq.…”
Section: Nuclear Magnetic Resonance (Nmr): Quadrupolar Splitting and mentioning
confidence: 99%